Upregulation of Nrf2/Ho-1 Signaling and Protective Effect of Melatonin Against Melphalan-Induced Reproductive Toxicity - Omolara, Ojo Olajumoke; Tosin, Ogunbiyi Babafemi; Faith, Adeosun; Ayegbusi, Emmanuel. O. (European Journal of Applied Sciences, 2024)
Oxidative stress occurs when there is an imbalance between the production and accumulation of reactive oxygen species (ROS) in cells and tissues and the ability of a biological system to detoxify these reactive products. The effect of Nrf2/HO-1 signalling improvement by melatonin on melphalan induced testicular dysfunction in mice was investigated. Thirty-six male Swiss albino mice were used for this study. Male mice were divided into six groups of six animals each and treated by intraperitoneal injection as follows; Group I: Vehicle treated control; Group II: Melatonin alone; Group III: 1mg/kg/bwt MEP; Group IV: 3mg/kg/bwt MEP; Group V: 5mg/kg/bwt MEP; Group VI (5mg/kg/bwt MEP + 10mg/kg/bwt Melatonin) for twenty-eight days. Hormonal assessments, expression of Nrf2 and HO-1 genes and evaluation of other sperm parameters are the various investigation depicted in this study. The result shows an increase in DNA damage and Teratozoospermia index (TZI). Raised level of malondialdehyde (MDA) and decreased level of Total antioxidant capacity (TAC) were measured. The result demonstrated ROS accumulation in the melphalan-treated groups, the result of this study also showed a decrease in testosterone levels, LH and FSH levels, decreased sperm concentrations and increased ROS upon administration of melphalan. Administration of melatonin to mice in Group VI showed a significant increase in the level of these hormones and antioxidant when compared to mice treated with melphalan alone. Therefore, it can be hypothesized that melphalan effectuated oxidative stress in the testes by disrupting Nrf2/HO-1 signaling pathway. This study found that melatonin is a potent regulator of Nrf2 and HO-1 in melphalan induced testicular dysfunction.